TOLERANCE IN THE REALM OF SCIENCE - Kuzmenko, Raisa (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
The article examines the features of the phenomenon of tolerance in the scientific field, its essential characteristics, and the main features of its philosophical interpretations. The actualization of the study of the problem of identifying tolerance in the field of scientific activity is caused by the rapid transformation processes at both the global and national levels associated with the transition of developed countries to the technologies of the fourth industrial revolution. It is substantiated that tolerance is one of the key principles of effective development of scientific sphere, and the creative activity of a particular subject of scientific activities. Progress in various fields of education and science, and the development of democratic relations in society depend on the manifestations of tolerance or intolerance to the opinion of the Other. Tolerant attitude to the Other contributes to the achievement of positive results in joint activities, encourages the discovery of new forms of communication, expanding contacts in the field science between scientists in the world and establishing partnerships.